Designated verifier ring signature and ring signcryption. (1st January 2013) - Fu, Xiaotong; Liu, Wen; Shi, Ruijun
Ring signatures can achieve the anonymity of the users who want to sign documents not only in the authenticated way but also in the confidential way. Based on the k-CAA2 assumption, a security designated verifier ring signature scheme is proposed from bilinear pairing. Furthermore, a designated verifier ring signcryption scheme is also proposed from the new designated verifier ring signature scheme.